Patrimonio cultural y museos como instrumentos de la educación entre pares. El caso de los embajadores del arte - Fernández-Inglés, Soledad (Studi sulla Formazione/Open Journal of Education, 2021)
This article is the result of an extensive research carried out in Spain and Italy to analyze the educational proposals and actions of the museums and teachers of the 4th year of Secondary Education around three transversal themes in education: art, cultural heritage and the culture of peace. The work I am presenting is a case study carried out in Florence (Italy) in which the Galleria degli Ufizzi participates as the formator of the Ambasciatori dell’Arte project, that responds to an innovative peer education strategy and has its origin in a previous project called Communicating Art.